Shared cognitions in a field of informal education: Knowledge maps towards money management of young adults - Barry, D.; Bender, N.; Breuer, K.; Ifenthaler, Dirk (2014)
Prerequisite knowledge of fi rst grade Bachelor students (N = 48) on processes of private consumption and housekeeping (money management) has been assessed by means of knowledge mapping. The study is based on the fact that in German compulsory education, there is no emphasis on economic literacy. Young adults (students), however, have to cope with individual economic planning processes. Most of them succeed based on support from families, friends, and peers. Some may simply refer to successful models experienced within their money socialization or to professional advice. Others, however, fail and become confronted with early indebtedness or even overindebtedness. The percentage of young adults with debtor carriers is growing. That evokes the claim for teaching fi nancial literacy through formal education within compulsory schools. Here, our research has its origin in the question for the knowledge base of young adults within the domain of fi nancial literacy. For going beyond knowledge on the level of simple recall, an approach of knowledge mapping is used. The underlying hypothesis is that despite of the common reference (given by the task and the relations), there will be no shared conceptual structures due to the lack of shared cognitions from formal education.